ANALISIS MEDIA MONITORING TERHADAP ISU TAPERA MELALUI MEDIA SOSIAL X - Prajna, Michelle; Abidin, Rohmad (Journal of Information System and Computer, 2024)
The use of the internet, including the use of social media, can change communication patterns, culture, and even information acquisition in everyday life. Social media not only functions as a tool for social interaction, but also as a platform for discussing current issues. One issue that is currently being discussed a lot is Tapera, namely a public housing savings program initiated by the government. However, the implementation of the Tapera program is not free from controversy and challenges. Various issues arise regarding the Tapera program, starting from its implementation mechanism, effectiveness, transparency, to fairness in the distribution of benefits from this program. To understand how the Tapera issue is discussed on social media X, it is necessary to carry out an analysis to determine the sentimen, frequency of mention and public reach regarding this issue. This research uses a qualitative descriptive method with a netnographic approach, utilizing the Brand24 media monitoring analysis tool to collect data from social media Therefore, the government is advised to consider more effective communication strategies to overcome negative perceptions and increase public acceptance of the Tapera program.